The Effect Of Leverage Level And Company Size On Profit Growth (Study On Food And Beverage Companies Listed On The Indonesian Stock Exchange (IDX) 2019-2023) - Nastiti Rizky Shiyammurti; Ersa Malani Karamoy (Jurnal Scientia, 2024)
The purpose of this study is ti test and analyze the the influence of leverage level and company size on profit growth in Food and Beverage companies listed on the Indonesia Stock Exchange for the period 2019-2023. The level of leverage is measured using the Debt to Equity Ratio (DER) and the company size measured using natural logarithms. The total sample used in this study is 18 companies through purposive sampling. The data used in this study in secondary data. To the test hypothesis in this study, a multiple linear regression analysis method with a result of the determination coefficient in this stydu is 50,5% which can be explained by independent variabels, namely leverage level and company size on the profit growth variable. The result of this study show that the level of leverage has a significant effect on profit growth. The level of leverage and the size of the company simultaneously affect the profit growth of food and beverage companies listed on the Indonesia Stock Exchange (IDX). Because the significance level is <0,0